History of Bengal as Reflected in the Tabaqat-i-Nasiri of Minhaj Uddin us Siraj - Sarkar, Anil Kumar (ASPENSI in Bandung, Indonesia, 2013)
ABSTRACT: We have had so far about Bengal history are from different sources that have defined the Bengal history from different angles, but no attempts have so far been made to treat the history of Bengal in the light of some specific medieval sources dealing with politics, administration, society, and economics of Bengal. In this respect, âTabaqat-i-Nasiriâ of Minhaj Uddin us Siraj is of immense importance to know about the history of this region. Incidentally, âTabaqat-i-Nasiriâ of Minhaj Uddin us Siraj also highlights a few points relating to the contemporary history of North Bengal (Varendri). Accordingly, Minhaj Uddin us Siraj has given an eyewitness account of the conquests of Ikhtiar-uddin Muhammad Bakhtyar Khalji in Bengal. In fact, the entire chapter in Bengal had centered on the military exploits of Bakhtyar Khalji. But what has been significant about his approach the thirteenth century Bengal history was kinness with which Minhaj Uddin us Siraj observed the contemporary social milieu. Besides giving the graphic description of every military encounter of Bakhtyar Khalji, Minhaj Uddin us Siraj always focused with curiosity on the social formation in Bengal. Minhaj Uddin us Siraj appeared to be particularly interested in describing military strategies. If one goes along the line of narration given by Minhaj Uddin us Siraj, it appears that Bakhtyar Khalji had used both military powers and strategic deception to conquer Nadia. Since Minhaj Uddin us Siraj stopped his narrative about Bengal with the incident of Bakhtiar Khaljiâs assassination, he did not mention any thing about the administration in Bengal. It is presumable that Bakhtiar Khalji did not get any time to organize his administration.KEY WORDS: Bengal history, Minhaj Uddin us Siraj, chronicle of âTabaqat-i-Nasiriâ, empire dynasties in India, eyewitness account, and contemporary social milieu.About the Author: Dr. Anil Kumar Sarkar is an Assistant Professor at the Department of History ABN (Acharya Brojendra Nath) Seal College, Cooch Behar, West Bengal, India. For academic interest, the author can be contacted via e-mail at: sarkaranil71@yahoo.inHow to cite this article? Sarkar, Anil Kumar. (2013). âHistory of Bengal as Reflected in the Tabaqat-i-Nasiri of Minhaj Uddin us Sirajâ in TAWARIKH: International Journal for Historical Studies, Vol.5(1) October, pp.1.29-42. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980.Chronicle of the article: Accepted (August 24, 2013); Revised (September 27, 2013); and Published (October 28, 2013).Â